Rubber powder-chicken feather fiber-stainless steel fiber composite modified geopolymer material and preparation method thereof

Through the composite modification of rubber powder, chicken feather fiber and stainless steel fiber, a tightly bonded mesh structure is formed, which solves the problem of insufficient mechanical properties and durability of geopolymer materials, and significantly improves the resistance to flexural, tensile, compressive and resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to resistance to The drying shrinkage performance extends the service life of building materials and realizes an environmentally friendly and economical production process.

CN119219370APending Publication Date: 2024-12-31NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411186731.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The lack of mechanical properties and durability of existing earth polymer materials leads to problems with durability and service life of building construction.

Method used

Using rubber powder, chicken feather fiber and stainless steel fiber composite modified polymer materials, a compact mesh structure is formed through specific raw material ratios and preparation processes to improve the material's resistance to flexion, tensile, compressive and drying and shrinkage. performance and enhance its thermal stability and weather resistance.

Benefits of technology

It significantly improves the mechanical properties and durability of geopolymer materials, extends the service life of building materials, and the raw materials are non-toxic, with a wide range of sources, and has no pollution in the production process, which has good economic benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a rubber powder-chicken feather fiber-stainless steel fiber composite modified geopolymer material and a preparation method thereof, and aims at solving the technical problem that an existing geopolymer material is insufficient in mechanical property and durability. The composite modified geopolymer material is prepared from the following raw materials in parts by weight: 300 parts of sand, 50-80 parts of slag powder, 20-50 parts of fly ash, 0.003-0.015 part of rubber powder, 0.1-0.3 part of chicken feather fibers, 0.15-0.30 part of stainless steel fibers and 20 parts of an alkali activator. The composite modified geopolymer material is excellent in performance, the preparation process is simple, the raw materials are non-toxic and harmless, meanwhile, the mechanical strength and durability of the geopolymer material can be improved, and the composite modified geopolymer material has great significance in prolonging the service life of a building material; the composite modified geopolymer material belongs to an environment-friendly composite geopolymer material, the raw materials are wide in source, the production process is free of pollution and low in price, and the composite modified geopolymer material has good economic and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of road engineering materials, and in particular to a geopolymer material compositely modified by rubber powder-chicken feather fiber-stainless steel fiber and a preparation method thereof. Background Art

[0002] As the overall level of my country's infrastructure has achieved a leapfrog improvement, environmental problems caused by massive energy consumption have also come along. Geopolymer is a type of green inorganic polymer that is more sustainable than cement in terms of energy required for production and low carbon emissions. It is an environmentally friendly building material. Its main feature is that most of the raw materials come from industrial waste, and compared with traditional silicate cement, it has the characteristics of low carbon emissions, fast setting, and early strength. Therefore, it is regarded as an environmentally friendly cementitious material that is more in line with the concept of sustainable development. However, due to the existing shortcomings of this type of material itself that need to be overcome, such as high brittleness, low toughness, and large crack width after cracking, cracks will continue to appear under the influence of external environmental factors, resulting in insufficient durability and bearing capacity of geopolymers, which in turn affects the durability and service life of building structures. Therefore, it is particularly important to develop a new type of modified geopolymer material to solve the durability problem.

[0003] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0004] The present application provides a geopolymer material compositely modified by rubber powder-chicken feather fiber-stainless steel fiber and a preparation method thereof, aiming to solve the technical problem of insufficient mechanical properties and durability of existing geopolymer materials.

[0005] According to one aspect of the present disclosure, a geopolymer material is provided, which is made of the following raw materials in parts by weight: 300 parts of standard sand, 50-80 parts of mineral powder, 20-50 parts of fly ash, 0.003-0.015 parts of rubber powder, 0.1-0.3 parts of chicken feather fiber, 0.15-0.30 parts of stainless steel fiber, and 20 parts of alkali activator.

[0006] In some embodiments of the present disclosure, the geopolymer material is made of the following raw materials in parts by weight: 300 parts of sand, 70 parts of slag powder, 30 parts of fly ash, 0.009 parts of rubber powder, 0.2 parts of chicken feather fiber, 0.2 parts of stainless steel fiber, and 20 parts of alkali activator.

[0007] In some embodiments of the present disclosure, the mineral powder is S95 grade slag powder.

[0008] In some embodiments of the present disclosure, the fly ash is Class II fly ash.

[0009] In some embodiments of the present disclosure, the sand is standard sand.

[0010] In some embodiments of the present disclosure, the alkaline activator is composed of a sodium hydroxide solution and a water glass solution with a modulus of 3 to 3.5 in a volume ratio of 3 to 4:1.

[0011] According to another aspect of the present disclosure, there is provided a method for preparing the above-mentioned geopolymer material, comprising the following steps: (1) removing impurities from the chicken feathers and collecting them, washing the collected chicken feathers and drying them at 100-110°C for later use; (2) Dry-mix rubber powder, chicken feather fiber, stainless steel fiber and sand for 1 to 2 minutes, then add mineral powder and fly ash and dry-mix for 1 to 2 minutes, and finally add water and alkali activator and stir for 2 to 3 minutes to form a uniform slurry; (3) Inject the slurry into the oiled mold and cure the mold under standard conditions; (4) After 20 to 25 hours, demould and continue curing to the specified age to obtain the composite modified geopolymer material.

[0012] In some embodiments of the present disclosure, in the step (4), after demoulding, the molded product is placed under standard curing conditions for curing.

[0013] In some embodiments of the present disclosure, in step (3), the standard curing conditions are a temperature of 18 to 22° C. and a relative humidity of ≥90%.

[0014] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. The geopolymer material of the present application is modified from composite fibers (rubber powder, chicken feather fibers, stainless steel fibers), and has excellent mechanical properties and durability. It can enhance the flexural strength, splitting tensile strength, anti-drying shrinkage and anti-freezing properties of the geopolymer material, and can effectively extend the service life of building materials. It is of great significance for solving the problems of large-scale energy consumption and shortage. Its raw materials are non-toxic and harmless, with a wide range of sources, and most of them are industrial waste. The production process is pollution-free and inexpensive. Its preparation process is simple and has good economic benefits.

[0015] 2. The rubber powder, chicken feather fiber, and stainless steel fiber in the geopolymer material of the present application can be tightly combined with the geopolymer matrix, so that they are irregularly distributed in the composite material to form a network structure, which has the function of a series skeleton. The addition of rubber powder can improve the toughness and energy absorption capacity of the geopolymer, and through its dispersion in the matrix, it plays a role in microcrack buffering and stress dispersion; stainless steel fiber can significantly improve the mechanical properties of the geopolymer, especially the tensile and compressive strength, due to its high strength and high modulus. At the same time, stainless steel fiber has good thermal stability, which can improve the overall thermal stability of the composite material and slow down the thermal degradation rate at high temperature; the natural hydrophilic groups contained on the surface of chicken feather fiber can enhance the interfacial bonding force with the geopolymer matrix. Both chicken feather fiber and rubber powder have high tensile strength and Young's modulus, which can effectively improve the shrinkage performance and compressive modulus of geopolymers. Chicken feather fiber will form a crack bridging effect in geopolymers to prevent or delay the expansion of cracks. Rubber powder absorbs energy in the stress concentration area generated at the crack tip and reduces the crack propagation rate. The two together control the expansion of cracks and improve the weather resistance and aging resistance of geopolymers. Stainless steel fiber can play its role of strengthening and toughening to enhance the mechanical strength of geopolymer materials, improve the wear resistance and chemical corrosion resistance of geopolymers, and extend their service life.

[0016] 3. The preparation process of the composite modified geopolymer material of the present application is to first dry-mix rubber powder, chicken feather fiber, stainless steel fiber and sand evenly, then add mineral powder and fly ash and dry-mix evenly, and finally add water and stir into a uniform slurry. This can ensure that the fibers are evenly dispersed in the geopolymer material, and the geopolymer material has better mechanical properties and durability. DETAILED DESCRIPTION

[0017] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0018] Unless otherwise specified, the pesticide and adjuvant raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, application methods and test methods involved are all conventional methods unless otherwise specified.

[0019] The composite modified geopolymer material in the following examples includes the following preparation steps: Prepare the raw materials according to the weight ratio of 300 parts of sand, 50-80 parts of slag powder (S95 grade slag powder), 20-50 parts of fly ash (II grade fly ash), 0.003-0.015 parts of rubber powder, 0.1-0.3 parts of chicken feather fiber, 0.15-0.30 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1); (1) After removing impurities from the chicken feathers, collect the chicken feathers, wash them with a detergent, and put them in an oven at 105°C to dry them for later use; (2) Dry-mix rubber powder, chicken feather fiber, stainless steel fiber and sand for 1 min, then add mineral powder and fly ash and mix them for 1 min, and finally add water and alkali activator and stir them into a uniform slurry for 2.5 min; (3) Inject the slurry into the oiled mold and cure the mold under standard conditions (temperature (20 ± 2) °C, relative humidity ≥ 90%); (4) After 24 hours, demoulding is performed and curing is continued in a constant temperature and humidity curing box under standard curing conditions until the specified age, thereby obtaining the preparation of the composite modified geopolymer material.

[0020] Example 1: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 60 parts of slag powder (S95 grade slag powder), 40 parts of fly ash (Grade II fly ash), 0.003 parts of rubber powder, 0.1 parts of chicken feather fiber, 0.15 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0021] Example 2: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 70 parts of slag powder (S95 grade slag powder), 30 parts of fly ash (Grade II fly ash), 0.006 parts of rubber powder, 0.15 parts of chicken feather fiber, 0.20 parts of stainless steel fiber, 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0022] Example 3: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.009 parts of rubber powder, 0.20 parts of chicken feather fiber, 0.25 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0023] Example 4: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.012 parts of rubber powder, 0.25 parts of chicken feather fiber, 0.3 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0024] Example 5: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.015 parts of rubber powder, 0.3 parts of chicken feather fiber, 0.3 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0025] Example 6: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.009 parts of rubber powder, 0.25 parts of chicken feather fiber, 0.25 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0026] Example 7: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.009 parts of rubber powder, 0.3 parts of chicken feather fiber, 0.3 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0027] Comparative Example 1: A common geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 60 parts of slag powder (S95 grade slag powder), 40 parts of fly ash (grade II fly ash), 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0028] Comparative Example 2: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.009 parts of rubber powder, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0029] Comparative Example 3: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.2 parts of chicken feather fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0030] Comparative Example 4: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (grade II fly ash), 0.25 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0031] Comparative Example 5: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.009 parts of rubber powder, 0.2 parts of chicken feather fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0032] Comparative Example 6: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.009 parts of rubber powder, 0.25 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0033] Comparative Example 7: A composite modified geopolymer material is made from the following raw materials in parts by weight: 300 parts of standard sand, 80 parts of slag powder (S95 grade slag powder), 20 parts of fly ash (Grade II fly ash), 0.2 parts of chicken feather fiber, 0.25 parts of stainless steel fiber, and 20 parts of alkali activator (sodium hydroxide solution and water glass solution with a modulus of 3.07 in a volume ratio of 3.74:1).

[0034] Mechanical properties and durability tests were carried out on the geopolymer materials in Examples 1-7 and Comparative Examples 1-7. The test items included flexural strength test, compressive strength test, splitting tensile strength test, drying shrinkage test and freeze-thaw cycle test to test the performance of the composite modified geopolymer material of the present invention and compare and analyze it with ordinary geopolymer materials. The test results are shown in Table 1.

[0035] Table 1 Mechanical properties and durability test indicators of various polymer materials .

[0036] As can be seen from Table 1, the 28-day flexural strength of the composite modified geopolymer material is greater than that of the ordinary geopolymer material, indicating that the toughness of the composite modified geopolymer material is stronger than that of the ordinary geopolymer material; the 28-day compressive strength of the composite modified geopolymer material is greater than that of the ordinary geopolymer material, indicating that the hardness and compressive resistance of the composite modified geopolymer material are stronger than those of the ordinary geopolymer material; the 28-day splitting tensile strength of the composite modified geopolymer material is greater than that of the ordinary geopolymer material, indicating that the crack resistance of the composite modified geopolymer material is stronger than that of the ordinary geopolymer material; the 90-day shrinkage rate of the composite modified geopolymer material is less than that of the ordinary geopolymer material, indicating that the volume stability and crack resistance of the composite modified geopolymer material are stronger than those of the ordinary geopolymer material; the 100-time mass loss rate of the composite modified geopolymer material is less than that of the ordinary geopolymer material, indicating that the extreme temperature damage resistance and durability of the composite modified geopolymer material are stronger than those of the ordinary geopolymer material. Compared with Comparative Examples 2-7, Example 3 has great advantages in all indicators.

[0037] The composite modified geopolymer material of the present application meets the relevant requirements of GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", JC / T 603-2004 "Test Method for Shrinkage of Cement Mortar", and JGJ / T 70-2009 "Test Method for Basic Properties of Building Mortar" standards, and its flexural strength, splitting strength and shrinkage performance indicators are significantly better than those of ordinary geopolymer materials, indicating that the performance of the geopolymer material of the present invention is superior.

[0038] The present application has been described in detail above in conjunction with the embodiments; however, those skilled in the art will appreciate that, without departing from the concept of the present invention, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.

Claims

1. A geopolymer material compositely modified by rubber powder-chicken feather fiber-stainless steel fiber, characterized in that: The invention is prepared from the following raw materials in parts by weight: 300 parts of sand, 50-80 parts of slag powder, 20-50 parts of fly ash, 0.003-0.015 parts of rubber powder, 0.1-0.3 parts of chicken feather fiber, 0.15-0.30 parts of stainless steel fiber and 20 parts of alkali activator.

2. The geopolymer material according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 300 parts of sand, 70 parts of slag powder, 30 parts of fly ash, 0.009 parts of rubber powder, 0.2 parts of chicken feather fiber, 0.2 parts of stainless steel fiber and 20 parts of alkali activator.

3. The geopolymer material according to claim 1, characterized in that: The sand is standard sand.

4. The geopolymer material according to claim 1, characterized in that: The slag powder is S95 grade slag powder.

5. The geopolymer material according to claim 1, characterized in that: The fly ash is Class II fly ash.

6. The geopolymer material according to claim 1, characterized in that: The alkaline activator is composed of a sodium hydroxide solution and a water glass solution with a modulus of 3 to 3.5 in a volume ratio of 3 to 4:

1.

7. A method for preparing the geopolymer material according to claim 1, characterized in that: The steps include: (1) removing impurities from the chicken feathers and collecting them, washing the collected chicken feathers and drying them at 100-110°C for later use; (2) Dry-mix rubber powder, chicken feather fiber, stainless steel fiber and sand for 1 to 2 minutes, then add mineral powder and fly ash and dry-mix for 1 to 2 minutes, and finally add water and alkali activator and stir for 2 to 3 minutes to form a uniform slurry; (3) Inject the slurry into the oiled mold and cure the mold under standard conditions; (4) After 20 to 25 hours, demould and continue curing to the specified age to obtain the composite modified geopolymer material.

8. The preparation method according to claim 7, characterized in that: In the step (4), after demoulding, the molded product is placed under standard curing conditions for curing.

9. The preparation method according to claim 7, characterized in that: In step (3), the standard curing conditions are a temperature of 18 to 22° C. and a relative humidity of ≥ 90%.